Challenges in addressing early stage laryngeal squamous cell carcinoma - Spector, Matthew E.; Rosko, Andrew J.; Birkeland, Andrew C. (Translational Cancer Research, 2018)
Laryngeal squamous cell carcinoma (LSCC) remains an important disease process worldwide, with over 150,000 cases diagnosed annually. Fortunately, most LSCCs overall are responsive to radiation (RT) and chemoradiation (CRT) therapies, which allows for preservation of the larynx structure and function. However, there remains room for improvement in RT/CRT protocols to achieve improved cure rates.